Formigas como indicadores ambientais na recuperação e conservação das margens do rio Uberabinha, Uberlândia, MG. - Leão, Ruthe Emília de Oliveira Saraiva (2019)
Urbanization is one of the current problems which global biodiversity is suffering. Its impacts may be loss of habitats and ecosystem services, fragmentation, biota homogenization and others. However, in urban areas there are green areas, which can be urban parks, backyards and gardens. These sites can act as reservoirs of native species in the city. Among insects, ants are a group widely used as bioindicators because of their wide geographical range and role in ecosystem services. The aim of this study was to verify, in an urban gradient, whether a reforested riparian zone will sustain greater species richness of ants than an adjacent non-reforested area (lawn). For six months, day and night collections of ants were carried out using sardine and honey baits in the soil. A total of 34 ant species were found, 17 occurred on the lawn and 33 in the reforested area. Ants richness was different among the sites, over the six months, with decrease in the dry periods of the year and between the periods of the day, with lower number of species at night. The differences in richness between sites are probably linked to environmental factors. The lawn is a homogeneous and exposed environment, with few resources while in the reforested area there is presence of trees in abundance, greater shading and accumulation of resources. Riparian zones are hot spots for maintaining biodiversity and are often the only green areas in cities. With the expansion of urbanization, reforestation of riparian zones can become an important tool for the conservation of invertebrate biodiversity even in urban areas.